The Correlation of Investment Securities and the Returns of Pension Fund Administrators in an Emerging Economy - Abdulrauf, Lukman Adebayo-Oke; Gbadebo, Adedeji Daniel (Ilomata International Journal of Tax and Accounting, 2024)
The pension fund administrators (PFAs) are saddled with the responsibility to manage and invest pension contributions on behalf of employees through investment in securities and the earnings from the investments. The PFAs are constantly faced with the problem of the optimization of financial performance of assets to make investment on. In line with theory, econometric offers the correlation frameworks as a simple and efficient way to resolve and understand the relationship between financial assets and financial returns. We applied the Pairwise correlation approach on published information of the National Pension Commission (PENCOM) during 2007 to 2021, to evaluate the connection between four financial assets that the PFAs in Nigeria invest in and the investment returns. In sum, two of the securities – money market securities and mutual funds – have positive relationship with the PFAs’ returns, and the other two considered – the federal government securities and private equity funds – have negative relationship with the PFAs’ returns. Only the correlation between the growth of investment return and investment in money market securities is moderate and significant, whereas others are low and insignificant, thus leading us to refute the first hypothesis, maintaining others. This offers insights into factors that affects their financial performance and investment strategies to be put in place to optimize return which in turn will benefit their contributors. The outcome provides policymakers and regulators with a comprehensive overview of the entire investment securities and performance of administrators.